Educational Robotics for Elementary Students: Teaching’s Opportunity - Nur Fitria, Tira (LPPM Universitas Terbuka, 2024)
This research describes educational robotics for elementary/primary students. This research is library research. The analysis shows that educational robotics (ER) can be introduced in elementary/primary schools, as it is compatible with subjects of Science, Technology, Engineering, and Mathematics (STEM). The benefits of educational robotics are enhancing higher-level thinking skills, computational reasoning, logical thinking, and problem-solving abilities. Robotics activities foster creativity and imagination, technological capabilities, teamwork, and collaborative skills, interest in technology culture, and skills development both motor and soft skills development. Educational robotics bridges the gap between students' learning and teachers' teaching methods, stimulating curiosity, interest, and motivation and also improving students' collaborative abilities and special needs education. By incorporating hands-on exercises, technological engagement, and collaboration, robotics can develop 21st-century skills. Educational robotics can help students with special needs by reducing teacher pressure and promoting personalized learning experiences. Therefore, the advancements in robotic technology make students more accessible and can be used as learning media to support their skills. However, educational robotics faces challenges in education including gender, teachers, teaching methods, curriculum, technology, resources, technical issues, teachers' lack of knowledge, teaching incentives, inadequate facilities and infrastructure, inadequate measures for successful integration, time, rules/regulations, and high costs.